Item Position Effects Are Moderated by Changes in Test-Taking Effort. (March 2017) - Weirich, Sebastian; Hecht, Martin; Penk, Christiane; Roppelt, Alexander; Böhme, Katrin
This article examines the interdependency of two context effects that are known to occur regularly in large-scale assessments: item position effects and effects of test-taking effort on the probability of correctly answering an item. A microlongitudinal design was used to measure test-taking effort over the course of a large-scale assessment of 60 min. Two components of test-taking effort were investigated: initial effort and change in effort. Both components of test-taking effort significantly affected the probability to solve an item. In addition, it was found that participants' current test-taking effort diminished considerably across the course of the test. Furthermore, a substantial linear position effect was found, which indicated that item difficulty increased during the test. This position effect varied considerably across persons. Concerning the interplay of position effects and test-taking effort, it was found that only the change in effort moderates the position effect and that persons differ with respect to this moderation effect. The consequences of these results concerning the reliability and validity of large-scale assessments are discussed.